Electrooptical complex for terrain on-time survey - S. B. Stukalov; D. S. Stukalov; V. I. Kondrikov; R. S. Gavryushin (Научный вестник МГТУ ГА)
The article deals with a number of approaches to the use of electrooptical systems and unmanned aerial vehicles (UAV) to solve the tasks of live terrain surface screening, air incident spots and objects survey. The paper provides the grounds for the UAV airframe chosen structure and the design of the electrooptical complex. The light weight, high -wing monoplane airframe structure is suggested. Using the CNC production center, a UAV with high aerodynamic performance was developed. The UAV was fitted with the optoelectronic system. Structural design for the airborne and ground equipment of the survey complex was developed. The structural design comprises the forward-looking and side airborne surveillance cameras and also downward-looking cameras of visible and infrared bands to provide the day and night vision. The downward-looking cameras of visible and infrared bands, integrated into the UAV fuselage belly are used for the surface monitoring and survey. The flight test on the use of electrooptic system comprised the flight on the route and automatic return using the satellite system navigation. The test showed that navigation data correction was required. The positioning accumulative error elimination is suggested to be done via automated image registration with the contour extraction and landmark reference. The image processing results using Canny algorithm were presented. The recommendations on the algorithm practical application and speed of response are given. To solve the problem of terrain on-time surveillance and monitoring the flight routes were subjected to research. Based on the experiments performed, the recommendations were given on the electrooptic complex application and flight route plotting for the tasks of on-time search and rescue.